Concurrent antipsychotic use in older adults treated with antidepressants in Asia. Issue 4 (7th February 2019) - Dong, Min; Zeng, Liang‐Nan; Zhang, Qinge; Ungvari, Gabor S.; Ng, Chee H.; Chiu, Helen F. K.; Si, Tian‐Mei; Sim, Kang; Avasthi, Ajit; Grover, Sandeep; Chong, Mian‐Yoon; Chee, Kok‐Yoon; et al.
Abstract : Aim: Depressive disorders are common in old age. Antipsychotics (APs) are often used as an adjunctive treatment with antidepressants (ADs) in this population but its patterns of use in Asia are not known. This study explored the rate of combination of APs and ADs in older adult psychiatric patients in Asia. Methods: This is a secondary analysis of the database of a multicentre study which recorded participants' basic demographical and clinical data in standardised format in 10 Asian countries and territories. The data were analysed using univariate and multivariate logistic regression analyses. Results: A total of 955 older adult psychiatric in‐ and outpatients were included in this study. The proportion of concurrent AP and AD use was 32.0%, ranging from 23.3% in Korea to 44.0% in Taiwan. Multivariate logistic regression analysis found that younger age, inpatient status and diagnosis of schizophrenia, anxiety and other mental disorders were significantly related to a higher proportion of concurrent use of APs and ADs. Conclusion: Around a third of older adult psychiatric patients had concurrent AP and AD use in the Asian countries/regions surveyed. Considering the uncertain effectiveness and questionable safety of the AP and AD combination in this patient population, such should be cautiously used.